Formation of Educational Activity - The Main Task of Primary Education (Texas Journal of Multidisciplinary Studies, 2023)
This article discusses the main tasks of primary education in improving the professional preparation of future primary school teachers for educational activities. It is known that Russian scientists V.V. Guzeev, V.V. Davidov, G.V. Dorofeev conducted fundamental scientific research with elementary school students on the problems of interaction and development. The fact that the elementary school, unlike the upper classes, has a fundamental scientific basis for the implementation of developmental educational ideas in education is scientifically based by the above scientists.